FIGURAS DE AUTORIDADE NO PROÊMIO DE ’TRABALHOS E DIAS’ | AUTHORITY FIGURES IN THE PROEM OF THE ’WORKS AND DAYS’ - Werner, Christian (Estudos Linguísticos e Literários, 2015)
Faz-se uma leitura cerrada do proêmio de Trabalhos e dias mostrando-se como a voz de Hesíodo se constitui a partir da autoridade das Musas e de Zeus, nesse sentido diferenciando-se este proêmio daquele da Teogonia. Abstract: A close reading of the proem of the Works and Days shows how Hesiod’s voice is constructed around the authority of Zeus and the Muses. This voice of Hesiod in the proem of the Works and Days stands in stark contrast to his approach in the proem of the Theogony.